Research on the association between beverages consumption and cancer - Waili, Alapati; Abdunayim, Shayidan; Talifu, Maidina; Zhuo, Zhaoxin; Ruzimaimaiti, Maidina; Tao, Liwen; Han, Wei (Frontiers in Medicine, 2025)
BackgroundCancer is the second leading cause of global death in the 21st century. Despite international efforts such as the European Code Against Cancer and the World Health Organization’s Global Action Plan, there are still significant gaps in translating policies into tangible outcomes. Diet, especially sugar intake, is a key modifiable factor affecting cancer risk, and the consumption of various beverages is associated with cancer susceptibility. This study uses bibliometric methods to analyze the research on the relationship between beverage consumption and cancer, aiming to provide a macro perspective and guide future research.MethodsWe searched for articles related to beverage consumption and cancer published between January 2005 and January 2025. Utilizing bibliometric methods, we analyzed the publications using R software, VOSviewer, and CiteSpace. Our analysis encompassed an examination of the publication volume, citation behavior, and co-authorship networks, aiming to reveal the research dynamics and trends within the field.ResultsWe conducted a bibliometric analysis of 998 articles and found that the number of publications related to beverage consumption and cancer has been increasing steadily year by year. Among many countries, the United States and China are the main contributors in this field. Among the top 10 institutions, the National Cancer Institute has published the most research results, with a total of 111 papers, indicating its significant influence in this research area. The citation bursts of keywords reveal that the current and future research focus is on exploring the complex relationship between specific dietary factors and various types of cancer.ConclusionExisting research indicates that over the past 20 years, there has been a steady increase in the number of research papers on beverage consumption and cancer. In this study, we conducted a comprehensive and impartial analysis of the relevant literature available in the WoSCC. We utilized various software tools to perform quantitative and visual analyses, such as examining the number of publications, citation counts, countries, institutions, journals, authors, cooperative relationships, and keywords. These findings enable researchers to identify emerging topics and frontiers in the field of beverage consumption and cancer, providing scholars with valuable insights and references.